Association between inflammatory cytokines and ADHD symptoms in children and adolescents with obesity: A pilot study. (August 2019) - Cortese, Samuele; Angriman, Marco; Comencini, Erika; Vincenzi, Brenda; Maffeis, Claudio
Highlights: ADHD and obesity are significantly associated. The characteristics of individuals with obesity at increased risk of ADHD need to be elucidated. We found a significant correlation between inflammatory cytokines and ADHD symptoms severity. These results pave the way for further role on the role of inflammatory mechanisms in the link between obesity and ADHD. Abstract: Whilst the association between Attention-Deficit/Hyperactivity Disorder (ADHD) and obesity is supported by meta-analytic evidence, the mechanisms underpinning this link need to be further elucidated. Inflammatory processes may increase the risk of ADHD symptoms in individuals with obesity. This pilot study set out to start testing this hypothesis by assessing the correlation between serum levels of inflammatory cytokines and ADHD symptoms severity in a sample of children and adolescents with obesity. We measured ADHD symptoms severity in 52 children/adolescents with obesity (BMI > 95th centile) with the Conners questionnaire, revised, short version, parent (CPRS-R:S) and teacher (CTRS-R:S) versions. Additionally, a categorical diagnosis of ADHD was established using the Kiddie-SADS-PL. Serum levels of IL-6, Il-10, and TNF-alpha were also obtained. The prevalence of ADHD was 9.6%. We found a significant correlation between IL-6, as well as TNF-alpha, and hyperactivity/impulsivity subscores of the CPRS-R:S and CTRS-R:S, that held even after controlling for BMI and oppositional symptoms. This study provides a rationale for larger, longitudinal studies to gain insight into inflammatory processes underpinning the link between obesity and ADHD. This line of research has the potential to lead to novel, pathophysiologically-based management strategies for individuals with obesity and ADHD.